MIMO wireless communications : from real-world propagation to space-time code design - Oestges, Claude (Academic Press, 2007)
Uniquely, this book proposes robust space-time code designs for real-world wireless channels. Through a unified framework, it emphasizes how propagation mechanisms such as space-time frequency correlations and coherent components impact the MIMO system performance under realistic power constraints. Combining a solid mathematical analysis with a physical and intuitive approach to space-time coding, the book progressively derives innovative designs, taking into consideration that MIMO channels are often far from ideal. The various chapters of this book provide an essential, complete and refreshin.